Measuring co-constructive collaboration between general and special education teachers in inclusive schools—development and validation of two short questionnaires - Kluge, Jacquelin; Korman, Benjamin A.; Schledjewski, Janine; Grosche, Michael (Frontiers in Psychology, 2025)
IntroductionCollaboration between general and special education teachers is important for the successful implementation of inclusive education. In this article, we discuss three forms of collaboration, with a particular focus on co-constructive collaboration as the most intensive and promising form for implementing inclusive education. Based on the theoretical framework of co-constructive collaboration, we validate two short questionnaires—in German as well as in English—for measuring co-constructive collaboration between general and special education teachers.MethodAcross six studies involving a total of 2.332 general and special education teachers, we conducted both exploratory and confirmatory factor analyses, examined convergent validity, and investigated whether the measurement model of our scales is invariant between (1) general and special education teachers, (2) primary and secondary school teachers, and (3) German- and English-speaking teachers.ResultsThe results reveal two reliable instruments: (1) one that assesses a comprehensive view of co-constructive collaboration, encompassing requirements, co-constructive activities, and outcomes, and (2) one that specifically measures teachers’ commitment to collaboration and iterative revision as a distinct co-constructive activity. The subscales largely correlate with related constructs, such as attitudes towards inclusion, confirming convergent validity. While measurement invariance is established for general and special education teachers, the results for the comparison between primary and secondary school teachers as well as between German- and English-speaking teachers are, with the exception of the latter group in the first instrument, less satisfactory. However, the respective factor structures of the individual groups are satisfactory.DiscussionThe findings demonstrate the reliability and validity of the newly developed instruments for measuring core-aspects of co-constructive collaboration between general and special education teachers in German- and English-speaking inclusive schools, supporting cross-cultural research in inclusive education. Study limitations, such as the partial lack of measurement invariance, are also discussed.